Real-World Effectiveness of Natalizumab in Korean Patients With Multiple Sclerosis - Kim, Ki Hoon; Kim, Su-Hyun; Park, Na Young; Hyun, Jae-Won; Kim, Ho Jin (Frontiers in Neurology, 2021)
Background and purpose: Natalizumab is a highly efficacious disease-modifying therapy for relapsing-remitting multiple sclerosis (MS). Data on the efficacy and safety profile of natalizumab in Asian patients with MS are limited. This study assessed the efficacy and safety of natalizumab in Korean patients with MS in a real-world setting. Methods: This study enrolled consecutive Korean patients with active relapsing-remitting MS who were treated with natalizumab for at least 6 months between 2015 and 2021. To evaluate the therapeutic outcome of natalizumab, we used the Expanded Disability Status Scale (EDSS) scores and brain magnetic resonance imaging; adverse events were assessed at regular intervals. No evidence of disease activity (NEDA) was defined as no clinical relapse, no worsening of EDSS score, and no radiological activities. Results: Fourteen subjects with MS were included in the study. The mean age at initiation of natalizumab therapy was 32 years. All patients were positive for anti-John Cunningham virus antibodies before natalizumab administration. The mean annual relapse rate was markedly reduced from 2.7 ± 3.2 before natalizumab therapy to 0.1 ± 0.4 during natalizumab therapy (p=0.001). Disability was either improved or stabilized after natalizumab treatment in 13 patients (93%). During the first year and 2 years after initiating natalizumab, NEDA-3 was achieved in 11/12 (92%) and 9/11 (82%) patients, respectively. No progressive multifocal leukoencephalopathy or other serious adverse events leading to the discontinuation of natalizumab were observed. Conclusions: Natalizumab therapy showed high efficacy in treating Korean patients with active MS, without unexpected safety problems.